Analysis of the moderating effect of media literacy on cervical cancer preventive behaviours - Arya Dharma Shinta; Mohd Azul Mohamad Salleh; Mohd. Nor Shahizan Ali (Penerbit Universiti Kebangsaan Malaysia, 2019)
Media literacy can be defined as the ability to access, assay, create, and interpret media messages which are therefore able to impact the beliefs and practices of their audience towards specific topics. In the field of health communications, the effects of media literacy can often be seen as the predisposing factor for health information acceptance towards preventive behaviours. Meanwhile, there are several moderating factors which could act as changing agents for media literacy so that it becomes the reinforcing factor and increases the resultant outcome of preventive behaviours. The initial focus of this study was to analyse the moderating factor of media literacy in regards to the cervical cancer preventive behaviour model by using PLS-SEM with smartPLS 3.0 statistical software. The analysis was conducted among 506 respondents with a formative research design. The findings indicated that the indirect effect of media literacy towards preventive behaviours, (p-value 0.038) with the level of education as a moderating factor (R2 0.14), significantly influenced the interactions occurring in the whole construct of the model. The result of the study is that level of education is revealed to have a significant effect as a moderating factor towards the acceptance of health information and media literacy in general, which in turn enhances the preventive behaviours on cervical cancer issues. These findings confirm that higher education is associated with ancillary benefits, one of which is the understanding of health issues and the resulting improved preventive behaviour outcomes.